Construct Validity and Reliability Testing of Perceived Job Stress as an Academic Leader (PJSAL) Instrument - Immanuel Yosua; Hana Panggabean (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2023)
This study aims to develop the Perceived Job Stress as an Academic Leader (PJSAL) instrument based on a modification of the Dean's Stress Inventory (DSI) instrument (Wild, et al., 2003). DSI is selected because it can accurately identify the potential sources of stress for a dean, which is also applicable in the context of academic leadership in general. This study involved 214 lecturers who responded to the PJSAL instrument via Google Form. Its construct validity was then assessed using Exploratory Factor Analysis (EFA), while its reliability was assessed based on Cronbach's Alpha values. The findings show that the PJSAL instrument has strong construct validity and good reliability (α = .965 for the entire instrument; α = .797- .918 for each subscale). The results of the EFA also reveal the existence of 10 factors in the PJSAL instrument, which are extracted from the 38 items composing it. The instrument is found not to be much different from DSI, except for the emergence of a new factor called role ambiguity.